Bronchiectasis and obstructive lung diseases in primary antibody deficiencies and beyond: update on management and pathomechanisms. Issue 6 (19th December 2022) - Hanitsch, Leif G.
Abstract : Purpose of review: Pulmonary complications are among the most frequent manifestations in patients with primary antibody deficiency (PAD), contributing significantly to morbidity and mortality. Here, we focus on recent findings in obstructive pulmonary disease and bronchiectasis in PAD. Since specific data on patients with PAD is limited and management mostly follows general recommendations, this review also aims to summarize data from the immunocompetent population. Recent findings: Potential risk factors for the development and progression of bronchiectasis include reduced immunoglobulins and lower CD4 cells. In addition, Pseudomonas aeruginosa and an altered microbiome might contribute to local inflammation and disease progression. Findings on the contribution of neutrophils and eosinophils in the affected immunocompetent population require confirmation in PAD. Despite its high global burden, there is an extreme paucity of data on chronic obstructive pulmonary disease in PAD. Lower IgA and IgM are associated with asthma in PAD, but the heterogeneity of prevalence among PAD groups is poorly understood. Recent observations of non-IgE-mediated pathomechanisms in asthma may be of particular interest in PAD patients. Summary: Management of PAD patients with chronic lung disease requires a multidisciplinary team approach including immunology, pulmonology, infectious disease and physiotherapy. Diagnostic processes should be harmonized to ensure a more precise perspective on prevalence and disease courses.